Pelatihan Pembuatan Krupuk Bunga Telang dan Daun Kelor di Desa Sedapurklagen Kecamatan Benjeng Kabupaten Gresik - Dwi Hardaningtyas; Nuraini Kusuma Andriyani; Alfi Nugroho (LPMP Imperium, 2025)
This activity was carried out to increase community empowerment in Sedapurklagen village, Benjeng, Gresik, which produces butterfly pea flower crackers and moringa leaf crackers. The business managed by Mrs. Pamiati has been running since 2018. During the Covid-19 pandemic, this business experienced a decrease in turnover because the public demand also decreased. After the pandemic, the demand for butterfly pea flower crackers and moringa leaf crackers increased so that it was necessary to expand the business that focus on improving the quality and capacity of production. The problem faced by partners in the production sector is that the crackers produced tend to be fragile. So far, the process of making crackers has been carried out in the traditional way, hand-stirred, the measurement of raw materials is based on habit. In terms of equipment, it is also inadequate and less hygienic. In addition, when the rainy season arrives, the cracker dough cannot be dried, so it tends not to produce crackers. This training was attended by 10 participants/residents of Sedapurklagen village on September 8, 2024 and mentoring was held on September 15, 2024. The result was that participants gained an understanding and knowledge about the health potential and business potential of butterfly pea flower crackers and moringa leaf crackers, so that participants had the opportunity to increase their family's economic income.